Comparison Of The Interferometric Performance For Spaceborne Parasitic SAR Configurations - Krieger, Gerhard; Wendler, Michael; Fiedler, Hauke; Mittermayer, Josef; Moreira, Alberto (EUSAR 2002, 2002)
The results of an interferometric performance analysis for spaceborne parasitic SAR configurations are presented. The analysis includes errors due to limited SNR, block adaptive quantization, range and azimuth ambiguities, and geometric decorrelation for both flat surfaces and random volumes. Relative height accuracies for three spaceborne configurations with PALSAR, ASAR and TerraSAR-X as illuminators are derived and compared.
DLR Import::2019-04-03